Μ‐Oxo‐Dinuclear‐Iron(III)‐Catalyzed O‐Selective Acylation of Aliphatic and Aromatic Amino Alcohols and Transesterification of Tertiary Alcohols. Issue 35 (28th July 2016) - Horikawa, Rikiya; Fujimoto, Chika; Yazaki, Ryo; Ohshima, Takashi
Abstract: A highly chemoselective and reactive μ‐oxo‐dinuclear iron(III) salen catalyst for transesterification was developed. The developed iron complex catalyzed acylation of aliphatic amino alcohols with nearly perfect O‐selectivity, even when using activated esters, for which chemoselectivity is more difficult to control. In addition, O‐selective transesterification of aromatic amino alcohols was achieved for the first time. The high activity of the iron complex enabled the use of sterically congested tertiary alcohols, including unprecedented tert ‐butanol. Abstract : High activity for sterics : A highly chemoselective and reactive μ‐oxo‐dinuclear iron(III) salen catalyst for transesterification was developed. O‐Selective transesterification of aromatic amino alcohols was achieved for the first time. The high activity of the iron complex enabled the use of sterically congested tertiary alcohols, including unprecedented tert ‐butanol.